Tolerance as an ethical issue with special reference to South Africa - Mnyaka, Mluleki Michael (Rhodes University, Faculty of Divinity, Department of Divinity, 1998)
From Introduction: It was a feature of South African political life to have senseless and continued political violence especially in areas such as KwaZulu Natal and Gauteng., There were certain places that were demarcated as "no-go areas" in other parts of the country for political rivals* This research has been directed by the cries of many South Africans pleading for political tolerance. Tolerance was a term used by both politicians and ordinary people alike and therefore open to misuse and various interpretations. As a term it was therefore without adequate clarification on its meaning. It is an attempt of this study to clarify and promote this value of tolerance. In Chapter One, the value of tolerance is examined. It is described as putting up with what is disliked or disapproved for the sake of others. But it is deliberate and is therefore a virtue. Positive attitudes, motives and power are central to tolerance. For tolerance to be sustained, solid foundations such as education, respect for others and their freedoms, democracy, justice, stability and reciprocity are to be laid. A light is also being shed on the limits of this virtue. Considerations and circumstances which need to be taken when deciding on each an action are the very motives and conditions for tolerance. This further makes the issue of tolerance to be complex. Church history shows that tolerance does not come naturally. It is a difficulty because of certain principles that are at stake. When viewed from the twentieth century perspective many of Church history's periods were of intolerance because the church had power. Tolerance was an exception, a plea of those without power. South Africa has to unlearn much of intolerance because of the past that militated against tolerance. Fortunately tolerance is now being firmly entrenched as law. Even though it is so, the tension of being tolerant and intolerant still exists especially in the whole area of abortion. Let us examine why tolerance is such a complex issue and a virtue to be promoted.
Keywords: Religious tolerance; Toleration; South Africa -- Constitution